A Meta-Analysis of Case Fatality Rates of Recurrent Venous Thromboembolism and Major Bleeding in Patients with Cancer - Abdulla, Alym; Davis, Wendy M.; Ratnaweera, Namali; Szefer, Elena; Ballantyne Scott, Brooke; Lee, Agnes Y. Y. (Thrombosis and Haemostasis, 2020)
Background Knowing the case fatality rates of recurrent venous thromboembolism (VTE) and major bleeding is important for weighing the relative risks and benefits of anticoagulation and deciding on the duration of anticoagulant therapy, but these rates are uncertain in patients with cancer-associated thrombosis.Methods We performed a systematic review and a meta-analysis to determine the incidence of recurrent VTE and major bleeding and their respective case fatality rates in patients with cancer-associated VTE.Results Our analysis included 29 studies (15 prospective cohort studies and 14 randomized controlled trials) from 1980 to January 2019. Data from 8,000 cancer patients with 4,786 patient-years of follow-up were summarized. Rates of recurrent VTE and fatal recurrent VTE were 23.7 (95% confidence interval [CI]: 20.1–27.8) and 1.9 (95% CI: 0.8–4.0) per 100 patient-years of follow-up, respectively, with a case fatality rate of 14.8% (95% CI: 6.6–30.1%). The rates of major bleeding and fatal major bleeding events were 13.1 (95% CI: 10.3–16.7) and 0.8 (95% CI: 0.3–2.1) per 100 patient-years of follow-up, respectively, with a case fatality rate of 8.9% (95% CI: 3.5–21.1%). While the estimates of case fatality vary by anticoagulation regimen and study design, the differences between them were not statistically significant.Conclusion In cancer patients receiving anticoagulation, the case fatality rate of recurrent VTE is higher than the case fatality rate of major bleeding. These findings may help to inform decisions regarding the management of anticoagulation in patients with active cancer and VTE.
Keywords: thrombosis; malignancy; clinical trials: heparins/low-molecular-weight heparin; clinical trials: oral anticoagulants